2018
DOI: 10.1123/smej.2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers and Sources of Support for Undergraduate Female Students’ Persistence in the Sport Management Major

Abstract: Male undergraduate sport management majors substantially outnumber females, suggesting that the path to a career in the sport industry is male dominated and gender stereotypes may exist. Simultaneously, there is a dearth of research on females’ experiences while enrolled in higher education and within sport management career development. Through qualitative focus groups conducted at two institutions with female sport management majors, this research sought to understand the barriers and sources of support that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, although gender equity education is a key component of many sports management education programmes (e.g. Sauder et al, 2018), the lack of mentoring for women moving into sports governance roles outside formal education is considered a problem, including amongst athletes (Schull, 2017) . The combined consequence of all the shortfalls and inequalities outlined above is the reproduction of unequal selection practices, or ‘access discrimination’, which can deny women access to positions (e.g.…”
Section: Research At the Macro-levelmentioning
confidence: 99%
“…For example, although gender equity education is a key component of many sports management education programmes (e.g. Sauder et al, 2018), the lack of mentoring for women moving into sports governance roles outside formal education is considered a problem, including amongst athletes (Schull, 2017) . The combined consequence of all the shortfalls and inequalities outlined above is the reproduction of unequal selection practices, or ‘access discrimination’, which can deny women access to positions (e.g.…”
Section: Research At the Macro-levelmentioning
confidence: 99%
“…Furthermore, female students felt they had to work harder than male students to overcome gender discrimination. Sauder, Mudrick, and DeLuca (2018) reaffirmed these findings in their study of perceived barriers and supports of female undergraduate sport management students. They found that the students felt a sense of otherness and were perceived as less credible.…”
Section: Review Of Literature Women In the Sport Management Majormentioning
confidence: 53%
“…Professors and mentors may also be able to influence future leaders to uphold and celebrate the presence and benefits of equality, equity, diversity, and inclusion in the workplace. This is illustrated in the findings of Sauder et al (2018) when they described the influence higher education has in supporting women students and encouraging inclusiveness in their classrooms. In addition to being fair and just, these principles make sense from the perspective of heightening organizational effectiveness (Desvaux et al, 2007;Torchia et al, 2018).…”
Section: Implications For Sport Management and Sport Leadershipmentioning
confidence: 99%
“…Finally, Sauder et al (2018) also utilized focus groups to gain the female sport management majors' perspectives on barriers and supports in the academic discipline of sport management. Four themes emerged from Saurder et al ( 2018) otherness, roles and credibility, prior experiences, and people of influence.…”
Section: Student Perceptions and Career Expectationsmentioning
confidence: 99%